If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17x + -1(8x + -4) = 13 Reorder the terms: 17x + -1(-4 + 8x) = 13 17x + (-4 * -1 + 8x * -1) = 13 17x + (4 + -8x) = 13 Reorder the terms: 4 + 17x + -8x = 13 Combine like terms: 17x + -8x = 9x 4 + 9x = 13 Solving 4 + 9x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 9x = 13 + -4 Combine like terms: 4 + -4 = 0 0 + 9x = 13 + -4 9x = 13 + -4 Combine like terms: 13 + -4 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| 5/6y=-20 | | -3x/8=-3 | | 2(5z+2)-6=88 | | (5x/8y^3)^2 | | x+24.8=48.5 | | 5(5x-1)=100 | | 40-2x=-38 | | 4x+9x-6x=42+7 | | 23=8x-9 | | 8-3n=n+4 | | -15x-60=-120 | | 10r+4=104 | | 0r+4=104 | | x+9=38 | | logx^2=8 | | -4y-6=1-3y | | -4x/5=60 | | -x+-x+-x+2=-x+-x+8 | | c+9=38 | | 3n-8=n+4 | | 19y-9=18y+27 | | 15=15x | | 447.104448(1609375/2442527)=x | | 38=x-9 | | 447.104448(2442527/1609375)=x | | 48.5=c-24.8 | | -5=17-x | | 3x^2-2x-15=-4 | | (5a-b)(6a+5b)= | | -.5x+1.5=.5 | | 5mn*6m= | | 2x^2-22x+28=0 |